FDI Spillovers and the Timing of Foreign Entry - Bruno Merlevede; Koen Schoors; Mariana Spatareanu (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2010)
This study analyzes the dynamic effect of FDI on local firms' productivity by relaxing the standard implicit assumption that technological spillovers are immediate and pfirmanent. We find that the entry of majority foreign owned firms has a short run negative effect on the productivity of local competitors, which is more than offset by a longer run positive effect. The entry of minority foreign owned firms has an immediate, though short-lived, positive effect on local suppliers through backward linkages. The entry of majority foreign owned firms also improves the productivity of local suppliers, but the effect materializes later and lasts longer.
Keywords: F2; 330; FDI; spillovers; dynamics; timing; Direktinvestition; Zeit; Spillover-Effekt; Produktivität; Verarbeitendes Gewerbe; Rumänien